CORPORATE ENTREPRENEURSHIP AND SERVICE FIRMS’ PERFORMANCE IN NIGERIA - Moruff Sanjo Oladimeji; Adebiyi Julius Abosede; Benneth Uchenna Eze (Economic Review)
The study examines the effect of corporate entrepreneurship (CE) as measured by innovation, risk taking, proactiveness, strategic renewal and corporate venturing on service firm non-financial performance as measured by market share, employee’s satisfaction, efficiency, productivity and workforce development. The study employed a survey research design through the administration of a structured questionnaire on 636 employees of 21 service firms, purposively selected. The questionnaire was validated by eight assessors (four academics and four management staff of service firms), in order to ensure that the instrument measures what it is designed to measure. The test re-test method was employed to test the reliability of the instrument, by conducting a pilot study, whereby, the questionnaire was administered twice within an interval of two weeks to 20 management staff of service firms, and the result of the two tests was correlated. This yielded a value of 0.78, which implies that the instrument is reliable. The data was analyzed with the aid of Stata12 and the findings reveal that CE elements account for 56% variation in service firm’s performance (Adj R-squared =0.5604). The findings further suggest that innovation, risk taking, proactiveness and corporate venturing significantly affect service firm performance, while strategic renewal does not significantly affect service firm performance. It is therefore recommended that in employing CE elements to enhance nonfinancial performance, service firm managers should focus on innovation, risk taking, corporate venturing and proactiveness, while strategic renewal should be employed cautiously.